Ecological Analysis of the Qur'an on Wildlife Protection and Biodiversity - Rahmawati, Artifah Tomi; Nirwana, Andri; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze the ecological perspective of the Qur'an in the context of wildlife and biodiversity protection through the approach of the Qur'an study. This study identifies ecological values and teachings that encourage human responsibility towards nature. The research method involves analyzing the text of the Qur'an related to the environment, wildlife, and biodiversity, focusing on concepts such as Khalifah (guardian of the earth) and Amanah (responsibility). This study also uses a semantic approach that is useful in analyzing the verses of the Qur'an on ecology. The study results indicate that the Qur'an contains values that support the protection and preservation of wildlife and biodiversity. The implications of these findings can provide a basis for developing environmental protection strategies rooted in Islamic values. This study is expected to better understand the relationship between religious teachings and biodiversity, lead to ecological awareness in everyday religious practices, and provide a basis for advocacy for nature conservation based on Islamic teachings.